Norsk Ordbok – om normeringa av Metaordboka - Svardal, Terje (Nordiske Studier i Leksikografi, 2003)
In this lecture I will discuss problems related to my work with Metaordboka, a normalised register of all lemmas represented in the paper slip archives underlying “Norsk Ordbok” - the original slip archives showing considerable variety in the rendering of one and the same lemma. My work on the Metadictionary has encountered mainly two types of problems. There are on one hand various problems related to the digitalisation of the archives, where f. i. poor paper quality makes the the digital archives difficult to read and interpret. On the other hand there are philological questions, varying from “spelling mistakes” to the normalisation of dialect material.